A texting‐based blood pressure surveillance intervention. Issue 10 (10th September 2019) - Zahr, Roula S.; Anthony, Chris A.; Polgreen, Philip M.; Simmering, Jacob E.; Goerdt, Christopher J.; Hoth, Angela B.; Miller, Michelle L.; Suneja, Manish; Segre, Alberto M.; Carter, Barry L.; Cavanaugh, Joseph E.; Polgreen, Linnea A.
Abstract: The authors examined whether using home BP measurements collected via a custom‐built bi‐directional‐texting platform incorporated into patients' electronic medical records would lead to treatment calibration and improved BP management. Patients were randomized to either the intervention group and collected home measurements based on reminders and reported via bi‐directional texting, or to the control group, with home BP measurement reporting via standard practice (eg, phone, electronic medical record portal) and instructed to return 7 morning and 7 evening BP measurements. Outcomes included number of BP measurements submitted, the number of medication changes, reduction in BP, and BP control. 72% of the intervention group submitted at least 14 readings, compared with 45% of the control group. BP control improved in both groups. However, the authors found no statistically significant difference in BP or the number of BP‐medication changes at 1, 3, or 6 months compared with the control group.